2021
DOI: 10.1155/2021/6658593
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, Toxicology, and Pharmacological Properties of Origanum elongatum

Abstract: Origanum elongatum L. is an endemic aromatic and medicinal plant. This work reports previous studies on O. elongatum concerning its taxonomy, botanical description, geographical distribution, bioactive compounds, toxicology, and biological effects. Chemical analyses showed that O. elongatum contains different chemical compounds, in particular volatile compounds. Pharmacological investigations showed that volatile compounds and extracts from O. elongatum exhibit different pharmacological properties, such as ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Despite this, only around 5%–15% of the roughly 250,000 higher plants have ever been studied for pharmacological activities [ 2 ]. Numerous studies conducted over the last few decades have shown that research on therapeutic plants is critical and bioactive phytochemicals or bionutrients are abundant in medicinal plants; these phytochemicals have a critical role in avoiding chronic illnesses such as cancer [ 3 5 ], diabetes [ 6 9 ], and coronary heart disease [ 10 12 ]. Dietary fiber, detoxifying agents, antioxidants, anticancer, neuropharmacological agents, and immune-stimulating agents are the key groups of phytochemicals having disease-preventive properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, only around 5%–15% of the roughly 250,000 higher plants have ever been studied for pharmacological activities [ 2 ]. Numerous studies conducted over the last few decades have shown that research on therapeutic plants is critical and bioactive phytochemicals or bionutrients are abundant in medicinal plants; these phytochemicals have a critical role in avoiding chronic illnesses such as cancer [ 3 5 ], diabetes [ 6 9 ], and coronary heart disease [ 10 12 ]. Dietary fiber, detoxifying agents, antioxidants, anticancer, neuropharmacological agents, and immune-stimulating agents are the key groups of phytochemicals having disease-preventive properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO, nearly 80% of the developing countries' population use traditional medicine as the primary source of therapy [ 18 ]. In Morocco, medicinal plants inhabit a significant room in medicinal systems and play an important part in the national economy [ 19 ], and numerous investigations showed recently remarkable results for future pharmaceutical applications [ 20 25 ]. Morocco is one of the Mediterranean countries with a long tradition of cultivating and using medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Origanum elongatum (Bonnet) Emb. & Maire (Lamiaceae) is an interesting non-threatened MAP species which is used to treat several diseases, and exhibits various biological activities such as antibacterial, antifungal, antiparasitic, antiviral, antioxidant, vasodilator, corrosion inhibitor, and hepatoprotective effects [ 48 ]. In addition, the essential oil of this species could preserve nutritional and organoleptic qualities, and is therefore suitable for food and culinary preparations [ 49 ].…”
Section: Discussionmentioning
confidence: 99%